Legal Protection on Pharmaceutical Product Patents by the Government on Covid-19’S Remdevisir and Favipiravir - Nurmawati, Bernadete; Iryani, Dewi; Setiawan, Puguh Aji Hari; Herman, KMS (International Journal Labs, 2022)
Background: The implementation of patents by the Government for pharmaceutical products can be carried out in terms of very urgent needs for the benefit of the community, such as medicines that are still protected by patents to overcome Coronavirus Disease 2019 (Covid-19) in Indonesia. Aim: To analyze the implementation of Patents by the Government according to Law Number 13 of 2016 concerning Patents and legal protection for pharmaceutical product patent holders for the Implementation of Patents by the Government against remdevisir drugs and favipiravir. Method: Research method based on normative juridical approach from various legal materials through literature studies. Findings: To overcome the Covid-19 disease in Indonesia, the government needs to establish an access policy for pharmaceutical products as stated in Presidential Regulation Number 100 of 2021 concerning the Implementation of Patents by the Government against Remdesivir Drugs and Presidential Regulation Number 101 of 2021 concerning the Implementation of Patents by the Government against the Favipiravir Drug, on November 10, 2021. Patent holders of Remdevisir and Favipiravir medicinal pharmaceutical products are entitled to legal protection for the exercise of exclusive rights and payment of compensation during the Implementation of Patents by the Government in the amount of 1% of the net selling value of Remdesivir and Favipiravir drugs.